The Concept of Legal Egalitarianism in Heterogeneous and Culturally Homogeneous Societies - I. V. Fedosov (Теоретическая и прикладная юриспруденция)
The article is devoted to the analysis of the concepts of legal egalitarianism and formal equality both in European legal orders and in legal orders of non-European cultural code in historical retrospect and modern times. The author traces the origin, emergence and development of the concept of formal equality and the accompanying philosophical and legal egalitarian doctrine that has gained dominant positions in the legal orders of European and other countries of the world after the French Revolution of 1789. The author examined historical material and scientific positions of various scientists — sociology, cultural science, social anthropology, political science, history and legal theory. The author reflects on the possibility and effectiveness of the uncontested existence and application of egalitarian legal doctrine in the context of complex heterogeneous multicultural societies. At the same time, the author questions the views on the essence of formal equality as a philosophical and legal concept and principle of law that exist in modern theoretical and legal studies.